Antibacterial Therapy of Severe Community-Acquired Pneumonia in Adults - Is There a Need for New Drugs? - S. A. Rachina; I. A. Zakharenkov; S. B. Yatsyshina; A. A. Bobylev; YU. V. Khruleva (Антибиотики и Химиотерапия)
Community-acquired pneumonia (CAP) is one of the most frequent acute infectious diseases in developed countries. Particular attention should be given to severe CAP, characterized by high mortality, high frequency of ineffectiveness of initial antibiotic therapy and treatment costs. The spread of pneumococcal isolates with reduced susceptibility to penicillin, III generation cephalosporins, macrolides, the risk of increasing the incidence of diseases caused by methicillin-resistant staphylococci and Enterobacteriaceae producing extended spectrum beta-lactamases (ESBL), led to a significant increase in interest in new antimicrobials (AMM) in CAP therapy. The review presents current data on the epidemiology and etiology of severe CAP (including trends in the antibiotic resistance of the main bacterial pathogens in the Russian Federation), outlines the basic principles of antibiotic therapy. The features of the activity spectrum, pharmacological characteristics, the results of clinical studies of the most promising antimicrobials - ceftaroline, solithromycin, new quinolones (dalafloxacin, nonmonoxacin, etc.), and omadacycline, are considered.